2005
DOI: 10.1105/tpc.105.036731
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis SOMATIC EMBRYOGENESIS RECEPTOR KINASES1 and 2 Are Essential for Tapetum Development and Microspore Maturation

Abstract: Among the >200 members of the leucine-rich repeat receptor kinase family in Arabidopsis thaliana, only a few have been functionally characterized. Here, we report a critical function in anther development for the SOMATIC EMBRYOGENESIS RECEPTOR KINASE1 (SERK1) and SERK2 genes. Both SERK1 and SERK2 are expressed widely in locules until stage 6 anthers and are more concentrated in the tapetal cell layer later. Whereas serk1 and serk2 single insertion mutants did not show developmental phenotypes, serk1 serk2 doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
241
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(262 citation statements)
references
References 46 publications
14
241
1
6
Order By: Relevance
“…BAK1 is involved in a light-dependent cell death [21], pathogenesis [4,6,24,29,46,51,54], and male sporogenesis [2,12]. These reports support the notion that BAK1 can act in a BRI1-independent way by binding to different LRR-RLKs which bind different ligands.…”
Section: Bri1-associated Receptor Kinase 1 (Bak1)supporting
confidence: 73%
“…BAK1 is involved in a light-dependent cell death [21], pathogenesis [4,6,24,29,46,51,54], and male sporogenesis [2,12]. These reports support the notion that BAK1 can act in a BRI1-independent way by binding to different LRR-RLKs which bind different ligands.…”
Section: Bri1-associated Receptor Kinase 1 (Bak1)supporting
confidence: 73%
“…The expression pattern of PhSERKs is reminiscent of their association with plant organ development as reported in other species. Moreover, AtSERK1 and 2 were reported to have redundant functions in sporophytic development and controlled male gametophyte production (Albrecht et al, 2005;Colcombet et al, 2005). Interestingly, PhSERK4 was preferentially expressed in pollinia as compared with other PhSERKs, and its expression peaked at the FB7 stage, when the anther was readily differentiated (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, transgenic Arabidopsis plants overexpressing AtSERK1 showed an enhanced capacity to initiate somatic embryogenesis during in vitro culture . Moreover, AtSERK1 and 2 play a role in male sporogenesis, particularly tapetum development (Albrecht et al, 2005;Colcombet et al, 2005). ZmSERK1 and 2 of maize are similar to carrot and Arabidopsis SERK genes and are expressed in embryogenic calli as well as male and female reproductive tissues (Baudino et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors [35][36][37] also found that RLK lectins appear to control the development of pollen development by regulating the endothecium, middle lamella and tapetum.…”
Section: Discussionmentioning
confidence: 99%